Case reportColorectal cancer in the course of familial adenomatous polyposis syndrome (“de novo” pathogenic mutation of APC gene): case report, review of the literature and genetic commentary - Stec, Rafał; Pławski, Andrzej; Synowiec, Agnieszka; Mączewski, Michał; Szczylik, Cezary (Archives of Medical Science, 2010)
Colorectal cancer (CRC) is one of the most common malignant tumours in Poland. Annually approximately 11 000 new cases of CRC are diagnosed, while the number of deaths caused by CRC approaches 8 000. Five-year survival does not exceed 20%. Familial adenomatous polyposis (FAP) is responsible for about 1% of new cases of CRC. The risk of CRC in FAP syndrome is 100%, and the average age of CRC development is 39 years. Early colectomy is the most effective method of CRC prevention. We report an atypical case of CRC in a patient with FAP caused by 2797-2800delAACA mutation of the APC gene.